THU0248 Patient-Oriented Decision of Early Treatment of Rheumatoid Arthritis with Combination of Triple Conventional Disease Modifying Anti-Rheumatic Drugs or Tumor Necrosis Factor Inhibitors and Methotrexate (Prospective, Open-Label Clinical Trial). (23rd January 2014) - Okada, M.; Matsuno, H.; Abe, C.; Katayama, K.; Kondo, M.; Sagawa, A.; Yamasaki, K.; Kishimoto, M.; Matsubara, T.
Abstract : Background: Early optimization of conventional disease modifying anti-rheumatic drugs (cDMARD) treatment is imperative as delay of biologics in certain patients can lead to irreversible functional disability. Bucillamine (BUC) is a unique cDMARD available in Japan in the past twenty years which was recently shown to augment the efficacy of methotrexate (MTX) and salazosulfapyridine (SASP) when they are administered together. Objectives: We examined the early institution of the triple combination therapy (TriD) before judging requirement of biologics by comparing to combination of TNF inhibitors and MTX (TNFI) in daily practice setting. Methods: 152 patients of early rheumatoid arthritis with worse prognosis based on the activity and known prognostic factors were incorporated in the study from 32 institutions belonging to Japan Association of Rheumatologists in Private practice (JARP). After careful informed consent, 114 patients by themselves decided to receive TriD therapy or TNFI therapy. Primary endpoint is average DAS28 score at 6 and 12 months, and secondary endpoint is clinical remission rate, functional remission rate and serum MMP-3 value at 3, 6 and 12 months, and modified Total Sharp Score at 12 months. Results: Sixty patients on TriD and 46 patients on TNFI completed 6 months treatment. Baseline DAS28 were 4.91±1.06 in TriD and 5.12±1.21 in TNFI (p=0.306). In 6 months the averages of DAS28 3.34±1.40 and 3.15±1.47 (p=0.470) in TriD and TNFI groups, respectively. EULAR Response and DAS28 at 3 and 6 months were also comparable and not statistically different. Image/graph: Conclusions: Patient preference to receive cDMARD or biologics after careful informed consent of treatment options can be acceptable in the first 6 months when another decision to switch therapy based on clinical and radiological evaluation in daily practice. This patient-oriented approach can lead to more patients satisfaction and reduction of medical cost. Disclosure of Interest: None Declared